ANALISIS LAJU PERTUMBUHAN PENDUDUK TERHADAP KETERSEDIAN SARANA DAN PRASARANA FASILITAS KESEHATAN DI KECAMATAN NANGGALO KOTA PADANG TAHUN 2014-201 - aditya alfikri Amanullah; Paus Iskarni (JURUSAN GEOGRAFI FIS UNP, 2020)
This reaserch aims to (1) find out the population growth rate in Nanggalo in 2014-2018 (2) to the availability of health facilities and infracstructure that is an accordance wuth the rate of population growth in Nanggalo. This reaserch used descriptive quantitative method, the use use of descriptive quantitative method in this reaserch is intended for acuquiring the information regarding the population growth rate in Nanggalo which then will be analyzed to discover how big the influence of population growth towords the availability of health facilities and infrastructure in Nanggalo. Based on the research result of the reasearch found that (1) Based on the data rangking from the rate growth of populationin year 2014-2018, it showed that Kurao Pagang with 40,14% population growth tobe the vilage with the highest population growth rate compared to other vilages in Nanggalo. Meanwhile, Surau Gadang had the lowest population growth with the percentage of -2,81%. (2) based on the data above, it can be concluded that availability of health infrastructure and facilities in accordance with the population growht was equally distributed to each vilage in Nanggalo except Kurao Pagang